2015
DOI: 10.1007/s00705-015-2403-5
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of eukaryotic elongation factor 1 alpha 1 (EEF1A1) in avian reovirus sigma-C-induced apoptosis and inhibition of viral growth

Abstract: Avian reovirus (ARV) causes viral arthritis, chronic respiratory diseases, retarded growth and malabsorption syndrome. It is well established that the ARV sigma-C protein induces apoptosis in host cells. However, the underlying molecular mechanism of this induction is still unclear. We report here the identification of eukaryotic elongation factor 1 alpha 1 (EEF1A1) as the interacting partner of σC. We found that σC-induced apoptosis in DF-1 cells could be completely abolished by knockdown of EEF1A1 by siRNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Four of these ten conservative amino acid mutations were located in the C-terminal fragment, which might contribute to differences among the ARV strains in their receptor-binding ability. In addition, ARV σC is known as an apoptosis inducer via interaction with eukaryotic elongation factor 1α1 (EEF1A1) 19 20 21 22 , and a domain including residues 210–246 of σC is involved in interactions with EEF1A1 19 . The conservative amino acid mutation at residue 221 might influence the interaction of σC with EEF1A1 and/or the induction of apoptosis by σC.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these ten conservative amino acid mutations were located in the C-terminal fragment, which might contribute to differences among the ARV strains in their receptor-binding ability. In addition, ARV σC is known as an apoptosis inducer via interaction with eukaryotic elongation factor 1α1 (EEF1A1) 19 20 21 22 , and a domain including residues 210–246 of σC is involved in interactions with EEF1A1 19 . The conservative amino acid mutation at residue 221 might influence the interaction of σC with EEF1A1 and/or the induction of apoptosis by σC.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is EEF1A1 (Elongation factor 1-alpha 1), which is involved in tRNA delivery to the ribosome, and is known to be activated upregulated upon inflammation [52]. This protein has been shown to physically interact to proteins of several viral species, specifically hepatitis delta [53] and avian reoviruses [54]; in the latter, knock-down of EEF1A1 has been shown to significantly impair the virus infection cycle. Therefore, the downregulation of EEF1A1 could be the result of an innate cell strategy to deprive SARS-CoV-2 of a key support for RNA replication.…”
Section: Human/covid-19 Interactome Response To Coronavirus Infectionmentioning
confidence: 99%
“…Recently, studies have shown that in addition to the role in protein translation, the two sister genes, eEF1A1 and eEF1A2, exhibit some non-canonical functions. eEF1A1 has been extensively studied [ 8 11 ], but eEF1A2 has not. eEF1A2, unlike eEF1A1 which is widely expressed, is mainly expressed in the brain, heart and skeletal muscle [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%